Evaluation of Factors Leading to the Development of Acute Pancreatitis at Tertiary Care Hospital, Karachi: Evaluation of Factors Leading to the Development of Acute Pancreatitis - Asif, Muneeba; Tariq, Faizan; Tarique, Faraz; Shah, Abdul Wadood; Soomro, Rukhsana; Zaman, Aliya (Pakistan Journal of Health Sciences, 2025)
Acute pancreatitis (AP) involves pancreatic inflammation that may extend to surrounding tissues. Clinical outcomes can be predicted through assessment of disease-specific prognostic markers. Objectives: To evaluate the prevalence of etiological factors for AP among patients at a tertiary healthcare center in Karachi. Methods: A descriptive cross-sectional design, this six-month study was conducted in the Medicine Department of Civil Hospital, Karachi, from 06-08-2022 to 05-02-2023. Participants were selected through convenience sampling (a non-probability approach). Data processing was done by SPSS version 26.0. Chi-square test was applied by taking a p-value of ≤ 0.05, which is significant. Results: The research cohort comprised 135 eligible participants with a mean age of 46.71 ± 6.82 years. Gender distribution showed 55 male patients (40.7%) and 80 female patients (59.3%). Out of the 135 patients, 43.7% had cholelithiasis, 11.1% had alcohol induced pancreatitis, 17.8% had post-ERCP pancreatitis, 14.8% had hypertriglyceridemia, and 10.4% had IgG4-mediated pancreatitis. Conclusions: Acute pancreatitis is a multi-factorial pathology of different severity and outcomes. Gallstones were found to be the most prevalent cause of the condition.